2021
DOI: 10.1177/23247096211056491
|View full text |Cite
|
Sign up to set email alerts
|

Beta Blockers as Salvage Treatment in Refractory Septic Shock Complicated With Dynamic Left Ventricular Outflow Tract Obstruction: A Rare Case Presentation

Abstract: Hypotension is the main finding in patients admitted to an intensive care unit (ICU) with the diagnosis of septic shock and it is related to worse outcomes. In these patients, several underlying causes of hypotension may co-exist, including vasoplegia, hypovolemia, drug-mediated venodilation, or myocardial dysfunction. Nowadays, echocardiography has been positioned as an essential tool in any ICU set to assess fluid status, ventricular ejection fraction, or any other myocardial complications. The high sympathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The authors used vasopressin at doses higher than routinely suggested (mean 0.06 IU/min, range 0.03–0.09 IU/min) to successfully reduce the dose of norepinephrine and improve the obstructive gradient in all patients [24]. Another recent case report demonstrated the successful use of intravenous esmolol to treat a patient with LVOTO in septic shock [25].…”
Section: Physiologicmentioning
confidence: 99%
“…The authors used vasopressin at doses higher than routinely suggested (mean 0.06 IU/min, range 0.03–0.09 IU/min) to successfully reduce the dose of norepinephrine and improve the obstructive gradient in all patients [24]. Another recent case report demonstrated the successful use of intravenous esmolol to treat a patient with LVOTO in septic shock [25].…”
Section: Physiologicmentioning
confidence: 99%